2002
DOI: 10.1007/s00464-001-8251-2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic antireflux surgery in the lung transplant population

Abstract: GERD occurs commonly in the posttransplant lung population. Laparoscopic fundoplication surgery, when indicated, can be done safely with minimal morbidity and mortality. In addition to the resolution of reflux symptoms, improvement in pulmonary function may be seen in this population after fundoplication. Lung transplant patients with severe GERD should be strongly considered for antireflux surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 16 publications
1
43
0
2
Order By: Relevance
“…It was confirmed that CF patients have an increased prevalence of acid reflux [21]. In addition, it has been shown that CF patients not only have acid but also nonacid reflux and, more often, proximal reflux when compared with other LTx recipients.…”
Section: Discussionmentioning
confidence: 82%
“…It was confirmed that CF patients have an increased prevalence of acid reflux [21]. In addition, it has been shown that CF patients not only have acid but also nonacid reflux and, more often, proximal reflux when compared with other LTx recipients.…”
Section: Discussionmentioning
confidence: 82%
“…Nissen fundoplication and Toupet fundoplication) can be performed safely on lung transplant candidates with advanced lung disease or lung transplant recipients with documented abnormal GOR [123,124,[127][128][129][132][133][134][135][136][137][138], thereby preventing reflux, aspiration of gastric secretions and related sequelae.…”
Section: Remarksmentioning
confidence: 99%
“…Антирефлюксное хирургическое лечение (напри мер, фундопликация по Ниссену или Тупе) может быть безопасно выполнено у кандидатов на тран сплантацию с поздними стадиями хронических ле гочных заболеваний или у перенесших трансплан тацию легких с подтвержденным ГЭР [123,124,[127][128][129][132][133][134][135][136][137][138]; тем самым предотвращаются дальнейший рефлюкс и аспирация желудочного со держимого и связанные с ними осложнения.…”
Section: рекомендацияunclassified